Znaczenie idei sprawiedliwego handlu dla krajów rozwijających się - Zajączkowski, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The purpose of this report is to show how the Fair Trade idea influences the social-economic situation in the Third World countries and to answer to the question how effectively it contributes to their economic growth. Empirical researches confirm that multilateral liberalization of the world trade could increase the world welfare. Simultaneously, countries that are isolated or show a passive attitude to the international trade indicate a lower economic growth. The promotion of the free trade and the stimulation of the economic growth are the stated aims of the World Trade Organization. However, the results of the trade liberalization, as pursued by the WTO, are not acceptable to the developing countries, whose social-economic situation is not improving significantly. Therefore, alternative solutions, which could solve the problem of developing countries from the South, are sought. It seems that one of the remedies would be the idea of the Fair Trade, which is the trading partnership between developed countries of the North and the marginalized producers and workers from the South, which is based on dialogue, transparency and respect and seeks a greater equity in the international trade.
Keywords: sprawiedliwy handel; kraje rozwijające się